1995
DOI: 10.1029/94ja02151
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of hydromagnetic chorus events at very high latitudes

Abstract: Hydromagnetic (HM) chorus events are ULF waves with typical frequencies from 0.2 to 0.6 Hz; their frequency‐time spectrum consists of a combination of band‐limited unstructured emissions and discrete elements. These waves are one of a class of short‐period ULF emissions (in the Pc 1 and 2 frequency range) that may be of value in ground‐based identification of the footpoint of magnetospheric boundary regions. As part of an extensive survey of Pc 1 and 2 waves at very high latitudes, we have identified all occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Popecki et al [1993] reported the same observation, from which they concluded that there was no solar effect on Pc 1-2 ground observations. The local time variations shown here are consistent with those observed in HM chorus events by Anderson et al [1995], and as in that study we suggest they may be caused by the offset between the magnetic and geographic poles, which may cause longitude-dependent effects.…”
Section: Statistical Studysupporting
confidence: 91%
“…Popecki et al [1993] reported the same observation, from which they concluded that there was no solar effect on Pc 1-2 ground observations. The local time variations shown here are consistent with those observed in HM chorus events by Anderson et al [1995], and as in that study we suggest they may be caused by the offset between the magnetic and geographic poles, which may cause longitude-dependent effects.…”
Section: Statistical Studysupporting
confidence: 91%
“…Omura et al [2010] theoretically showed that these EMIC waves with high-frequency sweep rate (e.g., 30 s/Hz in Pickett et al [2010]) are EMIC-triggered emissions caused by nonlinear frequency variations from the linear EMIC waves (the triggering EMIC waves) and the gradient of the background magnetic field near the magnetic equator. Similar rising tone structures have been observed on the ground, for example, as hydromagnetic emissions or hydromagnetic chorus [e.g., Fukunishi et al, 1981;Anderson et al, 1995], but timescales of those emissions (∼200-600 s) are much longer than those of EMIC-triggered emissions (several tens of seconds). The EMIC waves scatter magnetospheric protons, and those protons precipitate into the ionosphere to cause the proton 10.1002/2015JA021681 aurora [e.g., Yahnin et al, 2007;Sakaguchi et al, 2008;Nomura et al, 2012].…”
Section: Introductionmentioning
confidence: 52%
“…The predominant high‐latitude (L = 6–8) ground ULF signal near local noon is quasi‐structured hydromagnetic chorus/emissions [ Fukunishi et al , 1981; Menk et al , 1993; Anderson et al , 1995]. Since the early 1960s, it has been noted that the ULF waves on the ground near local noon were either turned on or enhanced in association with sudden impulses in the Earth's magnetic field [ Troitskaya , 1961; Heacock and Hessler , 1965; Kokubun and Oguti , 1968; Troitskaya et al , 1968; Hirasawa , 1981].…”
Section: Introductionmentioning
confidence: 99%